What do aggregate saving rates (not) show? - Alexey A. Ponomarenko; Alexey N. Ponomarenko (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The aggregate saving indicator does not directly reflect changes in individuals' microeconomic behavior. From the official statistics' point of view, households choose between spending, which generates additional income and consumption in the economy, and setting money aside, which does not. Formally, households may not (if the authors disregard housing investment) choose to save, because the aggregate saving statistical indicator is a residual concept defined as the ensuing difference between aggregate disposable income and consumption. It measures the change in net worth, which, in a closed economy, may only be generated by the production of capital goods and an increase in inventories. Using an agent-based model, the authors show that shocks unrelated to structural changes in households' behavior may generate positively correlated fluctuations in the aggregate saving rate, productivity growth and lending. Meanwhile, a genuine increase in the average individual propensity to save is not necessarily associated with a higher aggregate saving rate.
Keywords: C63; G21; O16; O40; 330; Saving; economic growth; credit; agent-based model; national accounts